Faktor-Faktor yang Memengaruhi Pulih Sadar Pasca Anestesi Inhalasi Desfluran dan Sevofluran di RSUD Majenang - Iqbal Anggi Afriansyah; Made Suandika; Mariah Ulfah (Universitas Malahayati Lampung, 2025)
ABSTRACT Consciousness is the awakening from the effects of anesthetic drugs after the anesthesia process and completion of surgery. Several factors that affect conscious recovery are the effects of anesthetic drugs, age, weight, duration of surgery, physical status and acid-base or electrolyte disorders. This study aims to determine the factors that affect conscious recovery after inhalation anesthesia desflurane and sevoflurane at Majenang Hospital. This study uses a quantitative method that is descriptive analysis with a Cross-sectional approach and two tests, namely the chi-square and mann-whitney tests. The sample in this study were all adult patients who underwent general anesthesia at IBS Majenang Hospital during the study period. The research data showed that the characteristics of the respondents were mostly adults 26-35 years old and the elderly aged 56-66 years old as many as 14.67% for desflurane, the largest female gender with desflurane use as much as 36%, BMI based on ideal body weight 18.5-24.9 kg / m2 with sevoflurane use as much as 38.67%. Furthermore, with a fast operation duration of 1 hour in the use of desflurane as much as 49.33% and a fast operation duration of 1 hour in the use of sevoflurane as much as 36%, the type of general anesthesia in respondents who recovered consciousness after desflurane inhalation anesthesia was 53.33% and sevoflurane as much as 46.67%, the Recovery Time of Consciousness was a fast recovery time of 15 minutes as much as 40% and in the use of sevoflurane with a fast recovery time of 15 minutes as much as 28%, The dose of inhalation anesthetic drugs used was 22 for desflurane and 36 for sevoflurane. After that, there was no effect of age, BMI, gender, type of inhalation agent and dose of anesthetic drugs on recovery of consciousness. The next result showed that there was an effect of the duration of surgery on recovery of consciousness after desflurane and sevoflurane inhalation anesthesia. Keywords: General Anesthesia, Sevoflurane and Desflurane, Recovery of Consciousness ABSTRAK Pulih sadar merupakan bangun dari efek obat anestesi setelah dilakukan proses pembiusan dan selesai tindakan pembedahan. Beberapa faktor yang mempengaruhi pulih sadar adalah efek obat anestesi, usia, berat badan, durasi operasi, status fisik dan gangguan asam basa atau elektrolit. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi pulih sadar pasca anestesi inhalasi desfluran dan sevofluran di RSUD Majenang. Penelitian ini menggunakan metode kuantitatif yang bersifat deskripsi analisis dengan pendekatan Cross sectional dan dua uji yaitu uji chi square dan mann whitney. Sampel dalam penelitian ini adalah seluruh pasien dewasa yang menjalani tindakan general anestesi di IBS RSUD Majenang selama periode penelitian. Data hasil penelitian menunjukan bahwa karakteristik responden mayoritas dewasa 26-35 tahun dan lansia akhir 56-66 tahun sebanyak 14,67%untuk desfluran, jenis kelamin perempuan terbanyak dengan pemakaian desfluran sebanyak 36%, IMT berdasarkan berat badan ideal 18,5-24,9 kg/m2 dengan penggunaan sevofluran sebanyak 38,67%. Selanjutnya dengan durasi operasi cepat 1 jam pada penggunaan desfluran sebanyak 49,33% dan durasi operasi cepat 1 jam pada penggunaan sevofluran sebanyak 36%, jenis general anestesi pada responden pulih sadar pasca anestesi inhalasi desfluran sebanyak 53,33% dan sevofluran sebanyak 46,67%, waktu Pulih Sadar waktu pulih sadar cepat 15 menit sebanyak 40% dan pada penggunaan sevofluran dengan waktu pulih sadar cepat 15 menit sebanyak 28%, penggunaan dosis obat anestesi inhalasi sebanyak 22 untuk desfluran dan 36 untuk sevofluran. Setelah itu tidak adanya pengaruh usia, IMT, jenis kelamin, jenis agen inhalasi dan dosis obat anestesi terhadap pulih sadar. Hasil selanjutnya menunjukan bahwa ada pengaruh durasi operasi terhadap pulih sadar pasca anestesi inhalasi desfluran dan sevofluran. Kata Kunci: General Anestesi, Sevofluran dan Desfluran, Pulih Sadar